Profesionalisme Dan Independensi Auditor Terhadap Kinerja Auditor - Puspanugroho, Erika Nofarisa; Muqorobin, Masculine Muhammad (Journal of Applied Accounting, 2022)
At this time, public trust in the public accounting profession began to diminish, this was due to the many cases of accounting manipulation. A Public accounting firm (KAP) is a public accounting organization that obtains a license in accordance with laws and regulations that operates in the field of providing professional services in public accounting practice. The auditor profession has been in the public spotlight in recent years. An auditor must have high professionalism in carrying out his duties. The audit results of an auditor must be accountable to interested parties. The auditor's performance is the result of the auditor's work in carrying out the assignment of examining the financial statements of an entity with the aim of determining the fairness of the financial statements. The quality of financial reports is centered on the auditor's performance. To achieve good performance, an auditor must have an attitude of independence. This study aims to determine how independence and professionalism affect auditor performance. The results of this analysis indicate that auditor professionalism and auditor independence have a positive effect on auditor performance. Based on these results, it can be concluded that an auditor who conducts audits in a professional manner will act independently so that the audit results cannot be influenced by other parties. Keywords: Professionalism, Independence, Auditor Performance